EFEKTIVITAS PROGRAM PARIRI LANSIA DAN PENYANDANG DISABILITAS DI KABUPATEN SUMBAWA BARAT - EFENDI, RUSTAM; UMAR, UMAR; SUPRIADI, DEDI (Universitas Mahasaraswati K. Mataram, 2023)
This research discusses the Effectiveness of the Elderly and Persons with Disabilities Pariri Program in West Sumbawa Regency. The objectives of this study are as follows: 1.To determine the utilization of social assistance from the Elderly and Persons with Disabilities Pariri Program by the beneficiaries. 2. To assess the social and economic impact of the social assistance from the Elderly and Persons with Disabilities Pariri Program on the beneficiaries. 3. To analyze the effectiveness of the social assistance provided by the Elderly and Persons with Disabilities Pariri Program. This research uses a mixed methods research approach. The study population consists of a total of 2,134 individuals, comprising 1,062 elderly individuals and 1,072 persons with disabilities. A sample of 308 individuals is selected using proportionate stratified random sampling. Data collection methods include interviews, questionnaires, and observations. The research findings indicate that the Elderly and Persons with Disabilities Social Assurance Pariri Program in West Sumbawa Regency effectively enhances the quality of life and meets the basic needs of the elderly. Additionally, it plays a crucial role in improving the quality of life and providing social protection to vulnerable groups. The program not only focuses on meeting basic needs but also has psychological, social, and economic impacts on the beneficiaries. The results of the independent t-test show that the p-values are 0.652 and 0.466 (both greater than 0.05) for the elderly and persons with disabilities, respectively, indicating insufficient evidence to reject the null hypothesis. The Elderly and Persons with Disabilities Pariri Program in West Sumbawa Regency is an effective program in meeting basic needs and has a significant impact on the recipients. The innovation of the Pariri Social Assistance Check Application has become an efficient tool for monitoring and optimizing the program's implementation.